Transformation of Historic Industrial Areas in Riga - Å olks, Guntis; Dejus, Gita; LegzdiÅ†Å¡, Krists (Mediterranean Journal of Social Sciences, 2012)
The aim of this research is to characterize the transformation processes of historic industrial areas in Riga. The research wasdone by using appropriate methods what include review of literature, field studies, expert interviews and GIS methods. Historic industrialareas comprise significant part of the built-up area in Riga and they form a specific urban environment in particular neighborhoods interms of historical and cultural heritage. These sites emerged and developed during the rapid industrial growth from 1860s to 1910swhen Riga became an important industrial centre of the Baltic region. These areas were mostly used for industrial purposes beforedeindustrialization after the collapse of the Soviet Union in 1991. Economic growth and construction boom in the early 2000s initiatedredevelopment and transformation of the historic industrial sites into premises for commercial, residential and retail use. Such urbanregeneration processes resulted in emergence of new desirable urban spaces while the number of urban brownfield sites decreased.However, significant part of historical and cultural heritage was lost, because in most cases preservation of these values was not topical.In this context urban regeneration processes have to be evaluated as an important approach for further urban development of Riga.